Penerapan Model Strategi Bisnis Pada Koperasi Syariah - S Sofiyanurriyanti (Department Industrial Engineering, University of Muhammadiyah Malang, 2017)
Koperasi BMT Syariah East Java is one of sharia-based cooperatives located in the area of Gresik, East Java. BMT cooperatives encountered many obstacles in society such as low awareness of the public in cooperatives, negative impression of the cooperative BMT, the level of customer confidence in the institution to be low, the limitations of market coverage and others. The matrices used in this study are IFE (Internal Factor Evaluation), EFE (External Factor Evaluation), CPM (Competitive Profile Matrix), SWOT, SPACE (Strategic Position and Action Evaluation), BCG (Boston Consulting), IE Matrix ( Internal-External), Grand Strategy Matrix, QSPM (Quantitative Strategic Planning Matrix) and Architecture Strategy. The results of this study are several alternative strategies such as Strategy 3 (S3), which is to improve the image of sharia cooperative BMT, Strategy 1 (S1) Increase participation, Strategy 6 (S6) establish partnership relationship with financial institution, Strategy 10 (S10) Product range and strategy 2 (S2) Expand the market. The next stage is the strategy architecture that is the stage toward the development stage, the stage of business development activities and the stage of maintaining the business. Strategy architecture stage is done by making short, medium and long term plan.